PET/CT studies of multiple myeloma using 18 F-FDG and 18 F-NaF: comparison of distribution patterns and tracers’ pharmacokinetics - Sachpekidis, Christos; Goldschmidt, Hartmut; Hose, Dirk; Pan, Leyun; Cheng, Caixia; Kopka, Klaus; Haberkorn, Uwe; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2014)
The aim of this prospective study is to evaluate the combined use of fluorine-18 fluorodeoxyglucose (18 F-FDG) and fluorine-18 sodium fluoride (18 F-NaF) PET/CT in the skeletal assessment of patients with multiple myeloma (MM) and to compare the efficacy of these two PET tracers regarding detection of myeloma-indicative osseous lesions.